NEW SOUTHBOUND POLICY 2.0 TAIWAN TERHADAP PENEMPATAN PEKERJA MIGRAN INDONESIA ANALISIS KONSTRUKTIFISME STUDI KASUS PEKERJA MIGRAN TAIWAN KABUPATEN KENDAL TAHUN 2023 -2025 - jumiat jumiat; Ali Martin; Sugiarto Pramono (CV Widina Media Utama, 2026)
This Studi is motivated by the implementation of the New Southbound Policy 2.0, which has increased the placement of Indonesian migrant workers in Taiwan, including those from Kendal Regency. However, migrant worker placement remains concentrated in the caregiving and domestic sectors, which are vulnerable to wage-related issues, contract violations, and inadequate legal protection. Studies examining the implementation of this policy at the local level also remain limited. Therefore, this Studi analyzes the implementation of the New Southbound Policy 2.0 in relation to the placement of migrant workers from Kendal Regency in Taiwan during the 2023–2025 period through a constructivist perspective. This research employs a qualitative method with a case Studi approach. Data were collected through observation, interviews, and documentation and analyzed through data collection, reduction, presentation, and conclusion-drawing stages. The findings indicate that the implementation of the New Southbound Policy 2.0 has increased the placement of migrant workers from Kendal Regency in Taiwan. Nevertheless, their employment remains dominated by the caregiving and domestic sectors, which are vulnerable to problems related to wages, employment contracts, and legal protection. Research on the implementation of this policy at the local level also remains limited. Therefore, this Studi examines the implementation of the New Southbound Policy 2.0 in the placement of migrant workers from Kendal Regency in Taiwan from 2023 to 2025 using a constructivist perspective. ABSTRAKPenelitian ini dilatarbelakangi oleh Implementasi New Southbound Policy 2.0 telah meningkatkan penempatan pekerja migran Indonesia ke Taiwan, termasuk dari Kabupaten Kendal. Namun, penempatan masih didominasi sektor caregiver dan domestik yang rentan terhadap persoalan upah, kontrak, dan perlindungan hukum. Kajian pada tingkat daerah juga masih terbatas. Karena itu, penelitian ini menganalisis implementasi NSP 2.0 terhadap penempatan pekerja migran asal Kendal ke Taiwan pada 2023–2025 melalui perspektif konstruktivisme. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis melalui tahapan pengumpulan data, reduksi, penyajian, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa, Implementasi New Southbound Policy 2.0 telah meningkatkan penempatan pekerja migran asal Kabupaten Kendal ke Taiwan, tetapi masih didominasi sektor caregiver dan domestik yang rentan terhadap persoalan upah, kontrak, serta perlindungan hukum. Kajian mengenai penerapan kebijakan tersebut pada tingkat daerah juga masih terbatas, sehingga penelitian ini menganalisis implementasi NSP 2.0 terhadap penempatan pekerja migran Kendal ke Taiwan periode 2023–2025 melalui perspektif konstruktivisme.